Duvalius (Neoduvalius) lohaji n. sp., a new remarkable subterranean taxon of the isotopic Trechini lineage from Dinaric karst, Bosnia and Herzegovina (Coleoptera: Carabidae: Trechinae) - Quéinnec, Eric; Ollivier, Eric (Zootaxa, 2021)
A morphologically distinguished and isolated cavernicolous trechine beetle belonging to the isotopic Duvalius lineage was discovered in Dinarids, Western Bosnia, in hypogean environment, in the cave Mračna Pećina. Duvalius (Neoduvalius) lohaji n. sp., is described, illustrated and compared with the other Duvalius species of the Dinaric range, especially with Neoduvalius taxa. In addition, taxonomical considerations about Duvalius-related genera that exhibit aphaenopsian morphology are given.